2006
DOI: 10.4028/www.scientific.net/msf.514-516.133
|View full text |Cite
|
Sign up to set email alerts
|

EPR and TEM Characterization of Electroluminescent Alq<sub>3</sub>

Abstract: EPR and TEM investigations on sublimated solid Alq3, [tris(8- hydroxyquinoline)aluminum(III)] are reported. Different paramagnetic centers in microcrystalline Alq3 fractions as synthesized and annealed are observed. Their nature, thermal treatment dependence, as well as correlation with the crystal structure are analyzed. The existence of randomly oriented triplets and quartets in annealed Alq3 fractions is evidenced from the temperature dependence of X- and Q-band EPR spectra. The spin Hamiltonian parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…This, in its turn, would enhance conduction with a faster rate. Super ionic conduction was also observed for KZC in the normal phase and it was attributed to a fast chemical exchange of K + ions between different, equivalent at high temperatures, sites [18,19]. + ion a process which would result in one free electron.…”
Section: Electrical Conductivitymentioning
confidence: 73%
“…This, in its turn, would enhance conduction with a faster rate. Super ionic conduction was also observed for KZC in the normal phase and it was attributed to a fast chemical exchange of K + ions between different, equivalent at high temperatures, sites [18,19]. + ion a process which would result in one free electron.…”
Section: Electrical Conductivitymentioning
confidence: 73%
“…Examples of room temperature EPR spectra are plotted in figure 7. A hyperfine structure due to the interactions with N and H nuclei was observed, partially resolved at low temperatures [25].…”
Section: Epr On Microcrystalline Alq 3 As Synthesizedmentioning
confidence: 94%
“…ε increased by ~10% of its value at the end of the heating run. This increase may be associated with a 'quick' annealing process that is due to the increase in the potassium ions mobility [2] and the fast chemical exchange between various equivalent K + sites found in the Nphase of KZC [6]. It can be also considered as a thermal lagging process due to which the sample needs time to reach its thermal stability.…”
Section: -4mentioning
confidence: 98%
“…In a comprativite EPR study of Mn +2 doped Rb 2 ZnCl 4 (RZC) and K 2 ZnCl 4 in the normal phase Grecu et al [2] found that K + ions became more mobile by raising temperature. During…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation